2013
DOI: 10.1038/ng.2760
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer patterns of somatic copy number alteration

Abstract: Determining how somatic copy-number alterations (SCNAs) promote cancer is an important goal. We characterized SCNA patterns among 4934 cancers from The Cancer Genome Atlas Pan-Cancer dataset. Whole-genome doubling, observed in 37% of cancers, was associated with higher rates of every other type of SCNA, TP53 mutations, CCNE1 amplifications, and alterations of the PPP2R complex. SCNAs that were internal to chromosomes tended to be shorter than telomere-bounded SCNAs, suggesting different mechanisms of generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

95
1,706
5
8

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,685 publications
(1,814 citation statements)
references
References 80 publications
95
1,706
5
8
Order By: Relevance
“…Alternatively, repetitive copy number alterations co‐occurring with mutations in driver genes could reduce BRAF and PIK3CA adjMAFs counts. However, the published literature does not support this hypothesis: BRAF and PIK3CA mutations rarely co‐occur with copy number gains in wild‐type alleles (The Cancer Genome Atlas, 2012; Zack et al ., 2013). Arm‐level 7q gains ( BRAF locus) have been described in up to 40% of CRC samples, mainly chromosomally instable tumors lacking BRAF mutations (The Cancer Genome Atlas, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, repetitive copy number alterations co‐occurring with mutations in driver genes could reduce BRAF and PIK3CA adjMAFs counts. However, the published literature does not support this hypothesis: BRAF and PIK3CA mutations rarely co‐occur with copy number gains in wild‐type alleles (The Cancer Genome Atlas, 2012; Zack et al ., 2013). Arm‐level 7q gains ( BRAF locus) have been described in up to 40% of CRC samples, mainly chromosomally instable tumors lacking BRAF mutations (The Cancer Genome Atlas, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…SCNAs in particular are the most intriguing form of genetic variations to study in cancer, as they alter the dosage of a gene product independent of the transcription factors and other controls. Analyses of cancer genome by cytogenetic studies and more recently by array hybridization profiling‐based methodologies have assisted in the identification of recurrent alterations unique to various cancers as well as some common alterations (Beroukhim et al ., 2010; Zack et al ., 2013). In understanding the role of CNAs, it becomes imperative to characterize the CNAs as the driver events in a particular malignancy and distinguish them from the passenger CNAs that would have been imbued into the genome during cancer evolution and possibly do not contribute towards it (Zack et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that CGRs are found in 5%-9% of all cancers (Malhotra et al 2013;Zack et al 2013) and ∼25% of bone tumors (Stephens et al 2011). However, these estimates depend on three factors: first, the type of data utilized (array or sequencing); second, the computational method implemented; and third, the specific types of cancer samples analyzed.…”
Section: Identification and Characterization Of Cgrs From Tcga Samplesmentioning
confidence: 97%
“…More recently, certain types of large-scale complex genomic rearrangements (CGRs), such as chromothripsis, breakage-fusion-bridges, and double minutes, have been discovered within tumor genomes and implicated in tumorigenesis ). CGRs involve three or more distant regions of the genome abnormally joining together and have been implicated in 5%-9% of all cancers (Malhotra et al 2013;Zack et al 2013) and ∼25% of bone tumors (Stephens et al 2011). These rearrangements can form distinct highly amplified contigs that harbor oncogenes, resulting in 10-to 100-fold increases in oncogene copy count, which may potentially drive tumorigenesis (Korbel and Campbell 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation